"With a little help I manage": helpful support for residents with chronic pan in long-term care - Matos, M.; Bernardes, S.F. (36th Annual Conference of the European Health Psychology Society, 2022)
Background: Up to 90% of the residents in long-term care facilities (LTC) suffer from chronic pain (CP), with major negative impacts on their psychological and physical functioning. Despite its prevalence and impact on LTC residents, CP is often underreported, underrecognized, under-assessed, and undermanaged. However, research has lacked to address the extent to which residents’ experiences with staff responses to their pain accounts for such outcomes. This qualitative study aimed to investigate residents’ subjective experiences of receiving pain-related social support and to identify which caregivers’ responses are perceived as helpful or unhelpful to pain adjustment. Methods: Data was collected through online individual semi-structured interviews and a thematic analysis was conducted. Twenty-nine LTC residents (7men, 22women, Mage=87.7) with CP, participated in this study. Findings: Two main themes emerged: (1) pharmacologic and non-pharmacologic support elicited and/or received to reduce pain during pain crisis; (2) Received pain-related instrumental support for activities of daily living (ADL). Overall, findings show that the most helpful support is protective of residents’ autonomy and embedded in connectedness. Also, supportive interactions were influenced by traditional gender roles. Discussion: By taking the care receiver perspective, this research brings novel contributions to the discussion on older adults’ reluctance to seek for and receive pain-related assistance, highlighting the role of resident-caregiver interactions. Furthermore, our findings bring practical contribution to the context of LTC by informing best care practices towards residents with CP.